Characterization and range of kerogen properties in the Vaca Muerta Formation, Neuquén Basin, Argentina. (March 2019) - Craddock, Paul R.; Mossé, Laurent; Bernhardt, Carolina; Ortiz, Alberto C.; Tomassini, Federico Gonzalez; Saldungaray, Pablo; Pomerantz, Andrew E.
Highlights: Kerogen properties are necessary to interpret downhole logs in evaluation of shale. Comprehensive set of kerogen properties from Vaca Muerta Formation is presented. Kerogen properties vary substantially and systematically with thermal maturity. Property-maturity relationships appear to be similar globally for type II kerogen. Results can be used to optimize log interpretation of oil- and gas-producing shales. Abstract: The Vaca Muerta Formation of the Neuquén Basin, Argentina, is a prolific oil- and gas-producing resource, characterized by high organic content and a large thermal maturity gradient running east to west. Kerogen properties are expected to vary substantially across the basin because of the range in thermal maturity (immature to dry gas). A comprehensive dataset of kerogen properties comprising thermal maturity, elemental composition, skeletal density, and specific surface area was acquired on cores from six wells. Kerogen isolates were prepared using a novel combination of acid demineralization and critical point drying that preserves the chemical and microstructural characteristics of kerogen. Kerogen properties are found to differ substantially between the studied wells, with variations correlating with thermal maturity. Kerogens show decreasing hydrogen content (H/C ratio ∼0.9–0.4) and nuclear hydrogen index (∼0.75–0.45), increasing grain density (∼1.28–1.55 g/cm 3 ), and increasing surface area (∼100–350 m 2 /g) during maturation. These properties can dominate the response of logging tools run in organic-rich mudrocks and are needed to properly interpret downhole logs run therein for appraisal of porosity, hydrocarbon volumes, and total hydrocarbon-in-place, for example.